PENDIDIKAN DAN PEMBERDAYAAN PEREMPUAN SEBAGAI MITRA SEJAJAR LAKI-LAKI - Amiruddin Amiruddin (P3M IAI Nusantara Batang Hari, 2016)
Education is a special thing only given tu human. Because it is only human can thraigh education. Education was essentially interded to form a perpect, human being human out wardly and inwardly, forming a happy human in the word and the here after. There fore, Islam considers that education is a right and a duty for every followers both men and women. This paper discurses how the image of women in the era of early education, namely education middle eastern woman approximately 14 centuries ago, and Indonesian women‟s education during the early era either before birth or arrival of Islam as well as after birth or arrival of Islam. it turned out that in the period before the islamic, education has not been fully enjoyed by women. The are considered hot so important to learn and they are placed in the number two position after men. After arrival of Islam, women get a fresh breeze and there are new colors for their. Women were given equal rights with men which in the end the degree they also raised as a human.Pendidikan adalah hal yang khusus hanya diberikan tu manusia. Karena hanya manusia dapat thraigh pendidikan. Pendidikan pada dasarnya interded untuk membentuk perpect, manusia manusia keluar wardly dan batin, membentuk manusia bahagia dalam kata dan di sini setelah. Ada kedepan, Islam memandang bahwa pendidikan adalah hak dan kewajiban bagi setiap pengikut laki-laki dan perempuan. Jurnal ini discurses bagaimana citra perempuan di era pendidikan awal, yaitu pendidikan wanita timur tengah sekitar 14 abad yang lalu, dan pendidikan perempuan Indonesia selama era awal baik sebelum kelahiran atau kedatangan Islam serta setelah lahir atau kedatangan Islam. ternyata bahwa pada periode sebelum Islam, pendidikan belum sepenuhnya dinikmati oleh perempuan. The dianggap panas sehingga penting untuk belajar dan mereka ditempatkan di posisi nomor dua setelah laki-laki. Setelah kedatangan Islam, perempuan mendapatkan angin segar dan ada warna baru bagi mereka. Perempuan diberi hak yang sama dengan laki-laki yang pada akhirnya gelar mereka juga dibesarkan sebagai manusia